2024: LAST YEAR’S BIGGEST INNOVATIONS IN HEALTH - Lavant, Agapi; Lalagkas, Romanos; Lymperopoulou, Irina (Open Schools Journal for Open Science, 2025)
The year 2024 witnessed ground-breaking advancements in healthcare technology, with new innovations reshaping the way we approach patient care and treatment. From brain implants that boost neural activity to artificial devices that can mimic the functions of a heart, these innovations have the capability to help numerous people in need. This paper explores the most significant of these technological breakthroughs and the individual stories behind them.